Perceiving, thinking, feeling, and doing Philosophy of Education (Foro de Educacion, 2017)
Do we need the Philosophy of Education? As the editors of this special issue we think that we need it. Educators and pedagogues must be aware of the reasons and aims behind what we do and the purposes of what we think. One possible step in this direction is based on breaking the logic by which the Philosophy of Education is inserted in the field of the theory and the abstractedness, and the pedagogical action in the field of practical issues and concrete problems. Therefore, at the beginning of our text we point out that in this special issue we aim at exploring the different ways of perceiving, thinking, feeling and doing philosophy of education and pedagogical action.